Macroeconomic theory - Vaish, M.C. (New Delhi: Vikas Publishing House, 1981)
The present edition has been completely updated. Every chapter has bee strengthened by incorporating the latest literature, replacing old diagrams and adding the new ones. Three new chapters -The Nature and functions of money, Supply of money and Monetarism - have been added n order to enrich the reader's understanding of these important subjects. In Part I the chapter on Basic concepts have been completely revised and strengthened as result of the incorporation of some new concepts, Similarly, chapters on National income and Social welfare, Income consumption relationship, Friedman's quantity theory of money and Creation and control of credit , to maintain only a few, have been almost recast.
Part I: Introduction -- Part II: Macroeconomic accounting -- Part III: Macroeconomic theory -- Appendix -- Part IV: Business cycle and growth
Keywords: Macroeconomics; Macroeconomic Theory